The politics of personal name: Naming and self-renaming among the Oromo of Ethiopia - Chala, Dejene Gemechu; Gutama, Workineh Diribsa (Nordic Journal of African Studies, 2019)
This article deals with the new trend of giving and changing personal names and self-naming among the Oromo in Ethiopia in the context of the post-1991 Ethiopian political landscape. The post-1991 situation indicates the ever-increasing introduction of new forms of Oromo personal names and the change of non-Oromo names into Oromo. Interview, focus group discussion, observation and document analysis were used to obtain qualitative data. The findings of the study indicate that there are various factors contributing to the introduction of new styles of crafting and changing personal names among the Oromo. These involve social values, political feelings, identity construction, personal benefit and various combinations of these. Yet there are still controversies on the social, political and linguistic implications of the newly emerging Oromo personal names. Some of our informants argued that the fashionable Oromo names do not sound like Oromo terms, both in their structure and pronunciation. They have veiled meanings (or are disguised names) with conflicting aspirations of returning to Oromo names on the one hand and disassociating oneself from conventional Oromo names on the other.